Study Of Types And Dosages Of Management On The Growth And Years Of Red Spinach (Amaranthus tricolor): Kajian Macam Dan Dosis Pupuk Kandang Terhadap Pertumbuhan Dan Hasil Tanaman Bayam Merah (Amaranthus tricolor) - Khomariyah, Nurul; Nurmalasari, Intan Rohma (Procedia of Engineering and Life Science, 2023)
Red spinach is a vegetable whose demand is very high, so further research is needed to increase theproduction quality of this commodity. The use of organic fertilizers such as manure can help increase the yield and growth of red spinach (Amaranthus sp) cultivation. This study aims to determine the effect of the use and a good dose for growth and obtain good results on red spinach (Amaranthus sp). This study used a randomized block design consisting of 2 factors and was repeated 3 times. The first factor was the type of manure, namely chicken manure and quail manure. The second factor is the dose of manure, namely the dose of 10 tons/ha, the dose of 20 tons/ha, and the dose of 30 tons/ha. From the results of the study, it was found that there was no significant interaction with all the red spinach measurement variables.